Hubungan Perkembangan Nilai Agama dan Moral dengan Perilaku Sosial Anak Usia Dini - Khaji, Khujatul; Yulianingsih, Yuyun; Ratnasih, Teti (JAPRA (Jurnal Pendidikan Raudhatul Athfal), 2020)
This study discusses the relationship between the development of religious and moral values with the social behavior of early childhood groups B RA PERSIS 235 Nasrullah Ujungberung Bandung. This research uses a quantitative approach with descriptive analytic methods that use correlation techniques. The subjects in this study were children of group B RA PERSIS 235 Nasrullah Ujung Berung Bandung in 2018/2019 Academic Year totaling 28 children. Data collection techniques used are observation, interviews and documentation. The results showed the development of religious and moral values of children of group B RA PERSIS 235 Nasrullah Ujungberung Bandung were in the high category with the acquisition of a value of 3.77 which was at an interval of 3.40 - 4.19. Social behavior of B RA PERSIS 235 Nasrullah Ujungberung Bandung children is in the high category with the acquisition of a value of 3.5 which is in the interval from 3.40 to 4.19. The relationship between the development of religious and moral values and social behavior of children of group B RA PERSIS 235 Nasrullah Ujungberung Bandung obtained a correlation coefficient of 0.83. Based on these results it can be concluded that there is a positive and significant relationship between the development of religious and moral values with social behavior of young children of group B RA PERSIS 235 Nasrullah Ujungberung Bandung with a very high level of relationship because it is in the interval of the correlation coefficient from 0.800 to 1,000.